Identifying the Benefits and Challenges of Digital Technology and Online Learning - Sharma, Lok Raj (International Research Journal of MMC, 2022)
Online learning, an internet-based learning, is also termed as e-learning which takes place in virtual environment. It has been possible due to the digital technology. It has become more influential in the recent years. We have not only been benefitted from this learning, but we have also undergone with its potent challenges. The principal objective of this research article is to identify the benefits and challenges of digital technology and online learning. This article is based on the qualitative research in which secondary data were basically taken from different journal articles. It is a review article prepared by going through the journal articles based on the digital technology and online learning. This article winds up with the conflicting remarks regarding the use of digital technology employed in online learning. Overcoming the challenges and difficulties of digitalization will undoubtedly result in learning efficiently.